Recycling method of environment-friendly lithium ion battery adhesive
By pulverizing and dissolving PVDF in organic solvents, and combining chemical modification of modified sodium alginate, maleic acid and hydroxyethyl acrylate, a polymer network structure is formed, which solves the problems of low recovery rate and insufficient performance in traditional recycling methods. It realizes efficient and environmentally friendly lithium-ion battery adhesive recycling and modification to meet the needs of high-performance lithium-ion batteries.
Patent Information
- Application Number
- CN202411376408.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2024-12-31
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional lithium-ion battery recycling methods have problems such as low recovery rate, high energy consumption, serious environmental pollution and insufficient performance of the recycled PVDF adhesive, which is difficult to meet the needs of high-performance lithium-ion batteries.
After pulverization treatment, mix it with organic solvent and heat to dissolve PVDF. It is separated by filtration and centrifugation, and the chemical modification of modified sodium alginate, maleic acid and hydroxyethyl acrylate is combined to form a polymer network structure to enhance the formation of adhesive. Membrane strength, heat resistance and mechanical strength.
It realizes efficient recycling and modification of PVDF, significantly improving the comprehensive performance of adhesives, meeting the needs of high-performance lithium-ion batteries, reducing environmental pollution and reducing resource consumption.
Smart Images

Figure CN119231003A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of battery recycling, and in particular to a method for recycling an environmentally friendly lithium-ion battery adhesive. Background Art
[0002] As the global demand for renewable energy continues to increase, lithium-ion batteries, as an efficient and clean energy storage device, have been widely used in electric vehicles, portable electronic devices, and energy storage systems. However, there are serious environmental problems in the production and disposal of lithium-ion batteries. In particular, waste lithium-ion batteries contain a variety of valuable materials, such as metals such as lithium, cobalt, and nickel, as well as polyvinylidene fluoride (PVDF) as an adhesive. If these materials are not handled properly, they will not only waste resources, but may also harm the environment and human health.
[0003] In the recycling process of waste lithium-ion batteries, the recycling of PVDF is particularly important. As a key adhesive for the positive and negative electrode materials of lithium-ion batteries, PVDF has excellent electrochemical stability and mechanical properties. However, traditional recycling methods often have problems such as low recovery rate, high energy consumption, and serious environmental pollution. On the one hand, due to the relatively low content of PVDF in waste batteries and its close mixing with other materials, it is difficult to achieve efficient separation; on the other hand, traditional recycling methods mostly use physical separation methods, such as crushing and screening, which not only have low recovery efficiency, but also easily introduce impurities, affecting the purity of PVDF.
[0004] In addition, if the recycled PVDF is directly used in the manufacture of new batteries, its performance is often difficult to meet the requirements of high-performance lithium-ion batteries. In particular, in terms of film strength, heat resistance, chemical corrosion resistance and mechanical strength, traditional recycled PVDF adhesives have obvious deficiencies; these problems limit the recycling of waste lithium-ion battery materials in battery manufacturing and also increase the production cost of new batteries.
[0005] Therefore, it is necessary to provide an environmentally friendly method for recycling lithium-ion battery adhesives to solve the above technical problems. Summary of the invention
[0006] The invention overcomes the shortcomings of the prior art and provides an environmentally friendly method for recycling an adhesive for lithium-ion batteries.
[0007] To achieve the above object, the technical solution adopted by the present invention is: a method for recycling an environmentally friendly lithium-ion battery adhesive, comprising the following steps:
[0008] S1: crush the waste lithium battery cells with voltage lower than the preset threshold, and the crushed particle size is less than 1mm;
[0009] S2: mixing the crushed material with an organic solvent, and heating and stirring within a specific temperature range to dissolve the polyvinylidene fluoride (PVDF) therein;
[0010] S3: filtering and centrifuging the mixture obtained in S2 to separate a pure PVDF solution;
[0011] S4: Mix soft water, emulsifier, maleic acid and hydroxyethyl acrylate and stir to form an emulsion; slowly add sodium alginate into the soft water, adjust the pH value after dissolving, spray acetic anhydride to react, and obtain a modified sodium alginate solution;
[0012] S5: emulsifying the modified sodium alginate solution, mixing it with the PVDF solution and emulsion obtained in S3, and stirring evenly;
[0013] S6: The mixed solution is heated and an initiator is added, and stirred to form a stable gel, which is then cooled to form an adhesive.
[0014] In a preferred embodiment of the present invention, in S2, the organic solvent is N,N-dimethylformamide (DMF) or dimethyl sulfoxide (DMSO), the solid-liquid ratio is 1:5-1:10, the heating temperature is 40-60°C, and the stirring time is 2-4h.
[0015] In a preferred embodiment of the present invention, in said S3, the pore size of the filter used for filtering is 0.1-0.5 μm.
[0016] In a preferred embodiment of the present invention, in S3, the rotation speed of the centrifugal treatment is 3000-5000 rpm, and the time is 10-20 min.
[0017] In a preferred embodiment of the present invention, in S4, the mass ratio of soft water, emulsifier, maleic acid and hydroxyethyl acrylate is 10:1:0.5:0.5, and the stirring time ranges from 20 to 40 minutes.
[0018] In a preferred embodiment of the present invention, in S4, after sodium alginate is dissolved in soft water at 50-60° C., the pH is adjusted to 8.0, and then acetic anhydride is sprayed into the water for reaction, and the pH during the reaction is maintained between 7.5 and 8.5. The reaction time of acetic anhydride is 1-2 hours.
[0019] In a preferred embodiment of the present invention, in S5, the emulsification treatment speed of the modified sodium alginate solution is 5000-10000 rpm, and the time is 60 minutes.
[0020] In a preferred embodiment of the present invention, in S5, the volume ratio of the emulsified modified sodium alginate solution and the PVDF solution is 1:1-1:3.
[0021] In a preferred embodiment of the present invention, in S5, the emulsion accounts for 5-10% of the total volume, is heated to 40-50°C during mixing, has a stirring speed of 200-300 rpm, and has a stirring time of 10 min.
[0022] In a preferred embodiment of the present invention, in S6, the temperature of the mixed solution is raised in the range of 60-70°C, and stirring is continued. After the solution becomes transparent and viscous, an initiator solution accounting for 0.5-1% of the total volume is slowly added dropwise.
[0023] The present invention solves the defects existing in the background technology and has the following beneficial effects:
[0024] (1) The present invention provides an environmentally friendly method for recycling lithium-ion battery adhesives, which can efficiently recover polyvinylidene fluoride (PVDF) from waste lithium batteries and significantly improve the various properties of the adhesive by adding modified sodium alginate; the method not only realizes the recycling of waste battery materials and reduces environmental pollution, but also enhances the film strength, heat resistance, chemical corrosion resistance and mechanical strength of the adhesive by chemical modification, thereby providing a more high-performance and environmentally friendly bonding solution for the manufacture of lithium-ion batteries; specifically, the present invention aims to achieve two core purposes: one is to efficiently recover PVDF from waste lithium batteries, and the other is to significantly improve the comprehensive performance of the adhesive by the interaction of modified sodium alginate with maleic acid and hydroxyethyl acrylate.
[0025] (2) In the present invention, the waste lithium battery cells are crushed, and organic solvents such as N,N-dimethylformamide (DMF) or dimethyl sulfoxide (DMSO) are used to heat and stir within a specific temperature range to effectively dissolve the PVDF in the cells. This step fully utilizes the good solubility of organic solvents in PVDF, combined with appropriate temperature and stirring conditions to ensure efficient dissolution and separation of PVDF. The efficient recovery of PVDF in waste lithium batteries is achieved with a high recovery rate and good purity, laying the foundation for subsequent modification and utilization. Compared with traditional recovery methods, the present invention avoids complex physical separation processes, improves recovery efficiency, and reduces energy consumption and costs.
[0026] (3) In the present invention, maleic acid and hydroxyethyl acrylate are introduced and chemically modified with sodium alginate to form a polymer network, which together with PVDF constitutes a complex interaction system; the polymerization or copolymerization reaction of maleic acid and hydroxyethyl acrylate, and the entanglement with the sodium alginate molecular chain, enhance the internal structure of the adhesive and improve its physical and chemical properties; significantly improve the film strength, heat resistance, chemical corrosion resistance and mechanical strength of the adhesive, making it more suitable for the manufacturing needs of lithium ion batteries; compared with traditional adhesives, the adhesive prepared by the present invention can better meet the needs of lithium ion batteries for high-performance adhesives; the excellent performance not only prolongs the service life of the battery.
[0027] (4) The present invention not only achieves efficient recovery of PVDF from waste lithium batteries, but also significantly improves the comprehensive performance of the adhesive through the interaction between modified sodium alginate and maleic acid and hydroxyethyl acrylate. This innovative recovery and modification method not only reduces environmental pollution and resource consumption; the high-performance adhesive provides strong support for the manufacture of lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art are briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative work.
[0029] Figure 1 It is a flow chart of a preferred embodiment of the present invention. DETAILED DESCRIPTION
[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein. Therefore, the protection scope of the present invention is not limited to the specific embodiments disclosed below.
[0032] like Figure 1 As shown, the present invention provides an environmentally friendly method for recycling lithium-ion battery adhesive, comprising the following steps:
[0033] S1: crush the waste lithium battery cells with voltage lower than the preset threshold, and the crushed particle size is less than 1mm;
[0034] S2: mixing the crushed material with N,N-dimethylformamide (DMF) or dimethyl sulfoxide (DMSO) at a solid-liquid ratio of 1:5-1:10, heating at 40-60°C, stirring for 2-4h, and heating and stirring within a specific temperature range to dissolve the polyvinylidene fluoride (PVDF);
[0035] S3: filtering and centrifuging the mixture obtained in S2, wherein the pore size of the filter used for filtration is 0.1-0.5 μm, the rotation speed of the centrifugation is 3000-5000 rpm, and the time is 10-20 min to separate the pure PVDF solution;
[0036] S4: soft water, emulsifier, maleic acid and hydroxyethyl acrylate in a mass ratio of 10:1:0.5:0.5 are mixed and stirred to form an emulsion, and the mixing and stirring time ranges from 20 to 40 minutes; after sodium alginate is dissolved in soft water at 50 to 60° C., the pH is adjusted to 8.0, and then acetic anhydride is sprayed into the reaction, and the pH during the reaction is maintained between 7.5 and 8.5. The reaction time of acetic anhydride is 1 to 2 hours to obtain a modified sodium alginate solution;
[0037] S5: emulsifying the modified sodium alginate solution at a speed of 5000-10000 rpm for 60 min, and mixing with the PVDF solution and emulsion obtained in S3 and stirring evenly, wherein the volume ratio of the modified sodium alginate solution to the PVDF solution after emulsification is 1:1-1:3, and the emulsion accounts for 5-10% of the total volume. During mixing, the temperature is heated to 40-50° C., the stirring speed is 200-300 rpm, and the stirring time is 10 min;
[0038] S6: The mixed solution is heated up and an initiator is added. The temperature of the mixed solution is raised to 60-70°C and stirred continuously. After the solution becomes transparent and viscous, 0.5-1% of the initiator solution of the total volume is slowly added dropwise and stirred to form a stable gel. After cooling, an adhesive is formed.
[0039] It should be noted that:
[0040] S1: The used lithium battery cells with voltage lower than the preset threshold are crushed to a particle size less than 1mm, which is conducive to the uniform mixing and reaction of substances in subsequent steps, improves the processing efficiency and material utilization rate, and reduces the potential safety hazards such as short circuit and leakage caused by the used battery cells through crushing.
[0041] S2: Use N,N-dimethylformamide (DMF) or dimethyl sulfoxide (DMSO) as solvent, heat and stir within a specific temperature range to effectively dissolve polyvinylidene fluoride (PVDF) in the battery cell, providing effect for subsequent separation and reuse. Reasonable solid-liquid ratio and temperature control ensure the efficiency of the dissolution process and the full dissolution of PVDF, avoiding solvent waste and unnecessary energy consumption.
[0042] S3: Through filtration and centrifugation, pure PVDF solution was successfully separated to provide raw materials for the subsequent preparation of adhesives. Appropriate filter mesh pore size and centrifugal parameters ensured the separation effect while avoiding the loss of PVDF and the mixing of impurities.
[0043] S4: Through a series of chemical reactions, a modified sodium alginate solution was successfully prepared to enhance the adhesion, stability and other properties of sodium alginate, providing better compatibility and performance for subsequent mixing with PVDF solution. The smooth progress of the modification reaction and the quality of the product were ensured by pH control and reaction time.
[0044] S5: The modified sodium alginate solution is emulsified, mixed with the PVDF solution and the emulsion, and stirred evenly to form a uniform mixed system, which lays the foundation for the subsequent preparation of a stable gel adhesive. Reasonable mixing ratios and conditions ensure sufficient mixing and reaction between the components, thereby improving the performance and stability of the adhesive.
[0045] S6: By increasing the temperature and adding the initiator, the mixed liquid forms a stable gel, and finally forms an adhesive after cooling. This process ensures the formation and curing of the adhesive, while controlling the performance and morphology of the adhesive. The appropriate amount of initiator and appropriate stirring conditions ensure the uniformity and stability of the adhesive formation, and avoid the generation of bubbles and defects.
[0046] The environmentally friendly lithium-ion battery adhesive recycling method of the present invention has the following advantages over the traditional adhesive recycling method:
[0047] 1. The polymer network of maleic acid and hydroxyethyl acrylate enhances the entanglement with sodium alginate, significantly improving the film-forming ability of the adhesive, making the surface coverage of the battery material more uniform and tight, and enhancing the overall structural strength and durability;
[0048] 2. The addition of modifier improves the internal structure of the adhesive and its interaction with PVDF, thereby enhancing both electrical conductivity and bonding strength, optimizing charge transfer within the battery, reducing internal resistance, and improving performance stability;
[0049] 3. The polymer network structure gives the adhesive excellent heat resistance and chemical stability, ensuring its excellent performance in extreme environments, improving battery safety and reliability, and extending service life.
[0050] Embodiment 1:
[0051] S1: Use a mechanical pulverizer to pulverize waste lithium-ion battery cells with a voltage lower than 2.5V, ensuring that the particle size of the pulverized material is less than 0.8mm to facilitate uniform mixing and reaction of the materials in subsequent processing.
[0052] S2: Mix the crushed material with DMF in a reactor at a solid-liquid ratio of 1:7, heat to 50°C, and stir continuously for 3 hours at this temperature. The stirring speed is controlled at 250 rpm to ensure that PVDF is fully dissolved in DMF.
[0053] S3: The mixture obtained in step S2 is first filtered using a filter with a pore size of 0.2 μm to remove large particle impurities; then centrifuged with the centrifuge speed set at 4000 rpm for 15 min to separate a pure PVDF solution.
[0054] S4: Weigh soft water, OP-10, maleic acid and hydroxyethyl acrylate in a mass ratio of 10:1:0.5:0.5, mix and stir for 30 minutes to form an emulsion. At the same time, dissolve sodium alginate in soft water at 55°C, and adjust the pH to 8.0 with sodium hydroxide. Subsequently, spray acetic anhydride under constant stirring to react, keep the pH of the reaction solution at about 8.0, and the acetic anhydride reaction time is 1.5 hours to obtain a modified sodium alginate solution.
[0055] S5: The modified sodium alginate solution is emulsified at a speed of 8000 rpm for 60 minutes. Subsequently, the emulsified modified sodium alginate solution is mixed with the PVDF solution and the emulsion obtained in S3, wherein the volume ratio of the modified sodium alginate solution to the PVDF solution is 1:2, and the emulsion accounts for 7% of the total volume. During mixing, the mixture is heated to 45°C, stirred at a speed of 250 rpm, and stirred for 10 minutes until a uniform mixed system is formed.
[0056] S6: The mixed solution is heated to 65°C and stirred continuously at this temperature until the solution becomes transparent and viscous. Subsequently, 0.75% of the total volume of ammonium sulfate solution is slowly added dropwise and stirred for 10 minutes until a stable gel-like substance is formed; finally, the gel-like substance is cooled to room temperature to obtain the desired environmentally friendly lithium-ion battery adhesive.
[0057] Embodiment 2:
[0058] Steps S1-S3 are the same as those in Example 1;
[0059] S4: using only soft water and sodium alginate, dissolving the sodium alginate and adjusting the pH to 8.0 according to a conventional method, without performing an acetic anhydride reaction, i.e., without introducing a modification step of maleic acid and hydroxyethyl acrylate;
[0060] Steps S5-S6 are the same as those in Example 1, but no emulsion is added in S5.
[0061] Embodiment three:
[0062] Steps S1-S3 are the same as those in Example 1;
[0063] S4: after dissolving sodium alginate and adjusting the pH, only maleic acid is added for reaction without adding hydroxyethyl acrylate to prepare a sodium alginate solution modified with maleic acid;
[0064] Steps S5-S6 are the same as those in Example 1, except that the preparation of the emulsion only includes the effect of maleic acid modification.
[0065] Embodiment 4:
[0066] Steps S1-S3 are the same as those in Example 1;
[0067] S4 (modified): similar to Example 3, but only hydroxyethyl acrylate was added to react to prepare a sodium alginate solution modified with hydroxyethyl acrylate;
[0068] Steps S5-S6 are the same as those in Example 1, and the preparation of the emulsion is adjusted accordingly.
[0069] Embodiment five:
[0070] Steps S1-S4 are the same as those in Example 1;
[0071] S5: The volume ratio of modified sodium alginate solution to PVDF solution was adjusted to 1:2, while the emulsion accounted for 7% of the total volume, and other conditions remained unchanged;
[0072] Step S6 is the same as that in the first embodiment.
[0073] Embodiment six:
[0074] Steps S1-S3 are similar to those in Example 1, except that DMF is replaced with dimethyl sulfoxide (DMSO) as the solvent, and other conditions remain unchanged;
[0075] Steps S4-S6 are the same as those in the first embodiment.
[0076] Experiment 1:
[0077] Film-forming property test: The adhesive prepared in each example was evenly coated on the surface of the battery material, and after drying under the same conditions, the film-forming conditions were observed, including the uniformity, density and adhesion of the film.
[0078] Subjective ratings were made on a scale from 0 (worst) to 10 (best) based on uniformity, density and adhesion of the film.
[0079]
[0080] Summary: Among all the embodiments, Embodiment 1 exhibits the best film-forming property, with a score of 9.75 points, which is much higher than other embodiments; its film layer is uniform, dense and has strong adhesion, providing good protection for battery materials.
[0081] Experiment 2:
[0082] Conductivity test: Apply the adhesive to a conductive substrate and measure its resistivity or conductivity after drying.
[0083] The unit is Siemens per centimeter (S / cm), which is calculated by measuring the resistivity. The lower the resistivity or the higher the conductivity, the better the conductivity.
[0084]
[0085]
[0086] Summary: Example 1 also performed well in the conductivity test, with a conductivity of 0.0161 S / cm, the highest among all examples; this shows that Example 1 has obvious advantages in conductivity and is helpful to improve the overall performance of the battery.
[0087] Experiment 3:
[0088] Adhesive strength test: Use a tensile testing machine to perform a tensile test on the battery material coated with the adhesive until it breaks, and record the maximum force at the time of break.
[0089] The unit is megapascal (MPa). It is found through tensile tests that the greater the breaking force, the higher the bond strength.
[0090]
[0091] Summary: Through the tensile test, Example 1 exhibited the highest bonding strength, reaching 12.56 MPa. This result verifies the effectiveness of Example 1 in enhancing the bonding force between battery materials, which helps to improve the stability and durability of the battery.
[0092] Experiment 4:
[0093] Heat resistance test: Place the sample coated with adhesive in a high temperature environment of 100°C for a certain period of time and observe its morphological changes and performance loss.
[0094] Heat resistance was evaluated by comparing the changes in properties before and after high temperature treatment.
[0095]
[0096] Summary: In a high temperature environment, Example 1 exhibits excellent heat resistance, and the bonding strength retention rate is as high as 95.94%. This result shows that Example 1 can maintain stable performance under high temperature conditions and is not prone to performance degradation, thereby extending the service life of the battery.
[0097] Experiment 5:
[0098] Chemical corrosion resistance test: Place the sample coated with adhesive in different chemical reagents (such as acid, alkali, salt solution, etc.) and observe its corrosion over a certain period of time.
[0099] Evaluation criteria: Subjective scoring based on mass loss, morphological change or performance loss before and after corrosion, ranging from 0 (worst) to 10 (best).
[0100]
[0101] Summary: In the chemical corrosion resistance test, Example 1 also performed well, scoring 8.80 points, ranking first; this shows that Example 1 has good resistance to a variety of chemical reagents and can maintain stable performance in harsh chemical environments.
[0102] Experiment 6:
[0103] Mechanical strength test: Use hardness tester, impact tester and other equipment to test the mechanical properties of samples coated with adhesive, such as hardness and impact resistance.
[0104] Mechanical strength score: A comprehensive score including hardness, impact resistance and other tests. It is also a subjective score ranging from 0 (worst) to 10 (best).
[0105]
[0106] Summary: Through the tests of the hardness tester and the impact tester, Example 1 also obtained the highest score in terms of mechanical strength, which is 9.50 points. This proves that Example 1 has excellent mechanical properties such as hardness and impact resistance, can withstand greater external impact and pressure, and further improves the reliability and safety of the battery.
[0107] In summary:
[0108] In this adhesive, maleic acid and hydroxyethyl acrylate undergo polymerization or copolymerization in solution, and the formed polymer network is tightly entangled with the sodium alginate molecular chains. This structure not only significantly enhances the strength and toughness of the film, but also gives the film layer the characteristics of uniformity, density and strong adhesion. It has a score of up to 9.75 points, providing a solid physical barrier and enhanced bonding force for battery materials, thereby improving the overall stability and safety of the battery.
[0109] At the same time, the copolymerization or cross-linking reaction between maleic acid and hydroxyethyl acrylate and PVDF forms chemical bonds at the break points or structural change areas of the PVDF molecular chain, effectively repairing and reinforcing these areas, further improving the performance of the adhesive, not only improving the heat resistance, chemical corrosion resistance, mechanical strength and electrical properties of PVDF, but also making Example 1 perform well in conductivity, with the conductivity reaching 0.0161S / cm, the best among all the examples, significantly reducing the internal resistance of the battery, and improving the current transmission efficiency and endurance.
[0110] In addition, the bonding strength of Example 1 is as high as 12.56MPa, which ensures the close bonding between battery materials and effectively prevents the materials from falling off or stratifying, thereby extending the service life of the battery; in a high temperature environment of 100°C, the bonding strength retention rate of Example 1 is as high as 95.94%, showing excellent heat resistance, enabling the battery to work stably in a high temperature environment and broaden the application scenarios.
[0111] In terms of adaptability to complex chemical environments, Example 1 also performs well and has good resistance to a variety of chemical reagents, with a score of 8.80 points, ranking first, allowing the battery to maintain stable performance under harsh chemical conditions. At the same time, its mechanical strength score of 9.50 points also proves its excellent performance in mechanical properties such as hardness and impact resistance, further improving the reliability and durability of the battery.
[0112] The above is based on the ideal embodiment of the present invention. Through the above description, relevant personnel can make various changes and modifications without departing from the technical concept of the present invention. The technical scope of the present invention is not limited to the content in the specification, and the technical scope must be determined according to the scope of the claims.
Claims
1. A method for recycling an environmentally friendly lithium-ion battery adhesive, characterized in that: The following steps are involved: S1: crush the waste lithium battery cells with voltage lower than the preset threshold, and the crushed particle size is less than 1mm; S2: mixing the crushed material with an organic solvent, and heating and stirring within a specific temperature range to dissolve the polyvinylidene fluoride (PVDF) therein; S3: filtering and centrifuging the mixture obtained in S2 to separate a pure PVDF solution; S4: Mix soft water, emulsifier, maleic acid and hydroxyethyl acrylate and stir to form an emulsion; slowly add sodium alginate into the soft water, adjust the pH value after dissolving, spray acetic anhydride to react, and obtain a modified sodium alginate solution; S5: emulsifying the modified sodium alginate solution, mixing it with the PVDF solution and emulsion obtained in S3, and stirring evenly; S6: The mixed solution is heated and an initiator is added, and stirred to form a stable gel, which is then cooled to form an adhesive.
2. The method for recycling an environmentally friendly lithium-ion battery adhesive according to claim 1, characterized in that: In the S2, the organic solvent is N,N-dimethylformamide (DMF) or dimethyl sulfoxide (DMSO), the solid-liquid ratio is 1:5-1:10, the heating temperature is 40-60°C, and the stirring time is 2-4h.
3. The method for recycling an environmentally friendly lithium-ion battery adhesive according to claim 1, characterized in that: In S3, the pore size of the filter used for filtration is 0.1-0.5 μm.
4. The method for recycling an environmentally friendly lithium-ion battery adhesive according to claim 1, characterized in that: In S3, the rotation speed of the centrifugal treatment is 3000-5000 rpm, and the time is 10-20 min.
5. The method for recycling an environmentally friendly lithium-ion battery adhesive according to claim 1, characterized in that: In S4, the mass ratio of soft water, emulsifier, maleic acid and hydroxyethyl acrylate is 10:1:0.5:0.5, and the stirring time ranges from 20 to 40 minutes.
6. The method for recycling an environmentally friendly lithium-ion battery adhesive according to claim 1, characterized in that: In the S4, after sodium alginate is dissolved in soft water at 50-60° C., the pH is adjusted to 8.0, and then acetic anhydride is sprayed in for reaction, and the pH during the reaction is maintained between 7.5-8.
5. The reaction time of acetic anhydride is 1-2 hours.
7. The method for recycling an environmentally friendly lithium-ion battery adhesive according to claim 1, characterized in that: In the S5, the emulsification treatment speed of the modified sodium alginate solution is 5000-10000 rpm, and the time is 60 minutes.
8. The method for recycling an environmentally friendly lithium-ion battery adhesive according to claim 1, characterized in that: In the S5, the volume ratio of the emulsified modified sodium alginate solution and the PVDF solution is 1:1-1:
3.
9. The method for recycling an environmentally friendly lithium-ion battery adhesive according to claim 1, characterized in that: In the S5, the emulsion accounts for 5-10% of the total volume, is heated to 40-50°C during mixing, has a stirring speed of 200-300 rpm, and a stirring time of 10 min.
10. The method for recycling an environmentally friendly lithium-ion battery adhesive according to claim 1, characterized in that: In the step S6, the temperature of the mixed solution is raised to 60-70°C and the mixture is continuously stirred. After the solution becomes transparent and viscous, an initiator solution accounting for 0.5-1% of the total volume is slowly added dropwise.
Citation Information
Cited By
Method for recycling PVDF (Polyvinylidene Fluoride) in positive plate of retired lithium ion battery and application
CN120978251A
